Fungi on Musa acuminata in Hong Kong - Photita W. (2014)
Results of an investigation into the fungi associated with dead tissue of Musa acuminata at two sites in Hong Kong are reported. Forty-six fungi were identified, comprising 14 ascomycetes and 32 mitospbric taxa (27 hyphomycetes and 5 coelomycetes). The frequency of occurrence of these fungi at the two sites was also investigated. The most common species was Memnoniella subsimplex which occurred on 70% of samples, followed by Verticillium sp. (48.75%) and Zygosporium oscheoides (47.5%). The mycota of the two sites differed significantly in species composition, although Memnoniella subsimplex, Nigrospora oryzae, Pyriculariopsis parasitica, Verticillium sp. and Zygosporium oscheoides were common at both sites. Durispora musae, Memnoniella subsimplex, Nigrospora oryzae, Pyriculariopsis parasitica and Verticillium sp. were restricted to the petioles, while Anthostomella clypeoides, Deightoniella torulosa and Hansfordia ovalispora were restricted to the leaves.